Evaluation of Industrial Waste in the Paints Industry Sector: Khartoum North Industrial Area - Ahmed, Mona Ali Mohamed (Journal of natural sciences, life and applied sciences, 2023)
The study focused on the management of industrial waste in the paints industry in the Khartoum North industrial area. The research material was collected through laboratory analysis of wastewater samples resulting from factories and subsequently compared with the instructions of the Sudanese standard board for wastewater.Through measuring the concentration of suspended microparticles in the production units and comparing them with occupational health instructions in addition to direct observation and a questionnaire-based exercise for factory departments.The results showed that the wastewater was discharged into the sewage network without adhering to the standards of the Sudanese standards board. Solid waste was disposed of in a landfill without treating of the hazardous waste, also factories do not treat the polluted air by the suspended particles.The paper recommended that there is a need to implement integrated environmental management of Sudan’s industry and keep pace with the global development in the field for combating industrial pollution from its sources and to encourage further research and studies in this area.
Keywords: Paints Industry; Industrial Waste Management; Wastewater; Suspended Particles; Sudanese Specification